Needlestick and sharps injuries in orthopedic surgery residents and fellows. (November 2019) - Snavely, Joseph E.; Service, Benjamin C.; Miller, Daniel; Langford, Joshua R.; Koval, Kenneth J.
Abstract: Objective: Needlestick and sharps injury (NSSI) is a common occupational hazard of orthopedic surgery training. The purpose of this study was to examine the incidence and surrounding circumstances of intraoperative NSSI in orthopedic surgery residents and fellows and to examine postexposure reporting. Design: A 35-question cross-sectional survey. Setting: The study was conducted by orthopedic surgery residents and faculty at a nonprofit regional hospital. Participants: The questionnaire was distributed to US allopathic orthopedic surgery residency and fellowship programs; 300 orthopedic surgery trainees participated in the survey. Results: Of 223 trainees who had completed at least 1 year of residency, 172 (77.1%) sustained an NSSI during residency, and 57 of 63 trainees (90.5%) who had completed at least 4 years sustained an NSSI during residency. The most common causes of NSSI were solid needles, followed by solid pins or wires. The surgical activity most associated with NSSI was wound closure, followed by fracture fixation. The type of surgery most frequently associated with NSSI was orthopedic trauma, followed by hip and knee arthroplasty. Of 177 trainees who had sustained a prior NSSI, 99 (55.9%) failed to report all events to their institution's occupational health department. Conclusions: The incidence of NSSI during residency training is high, with >90% of trainees in their fifth year or later of training having received an injury during their training, with a mean of >4 separate events. Most trainees with an NSSI did not report all of their events, which implies that changes are needed in the incident reporting process universally.